'Great, she's super-strong and she can alter time': Angel, visual pleasure and the cult action heroine. (March 2017) - Calvert, Bronwen
This article examines the character Illyria (Amy Acker) from the television series Angel (1999–2004). It examines Illyria as a representation of the 'cult' action heroine, and as a means of creating visual pleasure within the television narrative. In exploring her function within the narrative of Angel, in which her characterisation undercuts some common ways in which the female body is represented on-screen, the essay compares the character with other female action heroes of 1990s to 2000s television series.